2017
DOI: 10.1289/ehp641
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Substances during Pregnancy and Offspring Weight and Adiposity at Birth: Examining Mediation by Maternal Fasting Glucose in the Healthy Start Study

Abstract: Background:Certain perfluoroalkyl and polyfluoroalkyl substances (PFAS) are widespread, persistent environmental contaminants. Prenatal PFAS exposure has been associated with lower birth weight; however, impacts on body composition and factors responsible for this association are unknown.Objectives:We aimed to estimate associations between maternal PFAS concentrations and offspring weight and adiposity at birth, and secondarily to estimate associations between PFAS concentrations and maternal glucose and lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 69 publications
4
73
2
3
Order By: Relevance
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have examined the association of PFAS and birth size by infant sex, and most did not report differences by infant sex. Three studies found no interaction (Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017), while another study found interaction by sex only when examining dichotomous outcomes like low birth weight (Manzano-Salgado et al, 2017). Overall, the literature to date suggests PFAS may have little differential effect on fetal development by sex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the study reported inverse associations between maternal fasting glucose concentrations during pregnancy and PFASs, suggesting that reduced availability of maternal glucose reaching the fetus could be a potential mechanism linking PFAS exposure to reduced weight and adiposity at birth. [22]. In contrast, several studies did not find significant associations between PFASs and these birth outcomes [18, 19, 28, 29, 34].…”
Section: Fetal and Postnatal Growthmentioning
confidence: 98%
“…Though we are unable to probe the relationship between the human embryonic yolk and these parturition outcomes, the use of models such as the zebrafish may help to elucidate this relationship. Epidemiology studies have associated numerous environmental toxicants with reduced birth weight or size, including bisphenol A [81], phthalates [82], perfluorinated compounds [83, 84], and fine particulate matter [85]. However, the mechanisms underlying this relationship remain unknown.…”
Section: Uncovering the Role Of Embryonic Nutrition In The Developmenmentioning
confidence: 99%